The Effect of Live Streaming, Affiliate Marketing, and Fear of Missing Out on Purchasing Decisions at the TikTok Shop in Yogyakarta City - Nur Liana Safitri; Heri Prasetyo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research was conducted to review the influence of live streaming, affiliate marketing, and fear of missing out on purchasing decisions for TikTok Shop users in Yogyakarta City. This research applies a quantitative approach with multiple linear regression analysis methods. Data was obtained through distributing questionnaires to 100 respondents who had shopping experience at TikTok Shop. Based on the results of the analysis, it was found that partially the live streaming and affiliate marketing variables had a significant effect on purchasing decisions, while the fear of missing out did not show a significant effect. However, the three variables simultaneously proved to have a significant influence on purchasing decisions. A total of 56.9% of the variation in purchasing decisions was explained by the three variables, while the rest was influenced by other factors outside the model. This finding indicates that marketing strategies based on visual content and personalized approaches, such as live streaming and affiliate marketing, are more effective in influencing consumer decisions than emotional pressures such as fear of missing out. Therefore, the results of this research can be taken into consideration for businesses in developing more suitable promotional strategies on the TikTok Shop platform.